Partnership between teachers and parents to improve students' English communication skills - Stevanović Nenad J.; Trajković Anđelija M. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
The aim of the work is to examine the opinions of teachers and parents about partnership relations in order to improve students' communication skills in English. The research was conducted using two instruments specially constructed for the purposes of the research. The sample included 64 teachers and 65 parents from the territory of the Republic of Serbia. The obtained results show positive attitudes towards the development of partnership in both groups of respondents, but also the existence of a statistically significant difference between both groups, whereby the attitudes of parents are significantly more positive. The results of the research indicate the importance of the contribution of affirming positive interpersonal attitudes, both of teachers and parents, which are important in the establishment of partnership relations towards the improvement of students' communication skills in English as a foreign language. Regarding the limitations of the research, the research was conducted on a limited sample, so caution should be exercised when generalizing the results. It should also be taken into account that the teachers and parents surveyed are from different parts of the Republic of Serbia, so it is not possible to know whether there is a certain deviation depending on the region or municipality. It is recommended to conduct the research that include the students' views in the survey in order to get a more complete picture.